Chiral Phosphoric Acid‐Catalyzed Enantioselective Three‐ Component Aza‐Diels–Alder Reactions of Aminopyrroles and Aminopyrazoles. Issue 8 (9th April 2014) - Brioche, Julien; Courant, Thibaut; Alcaraz, Lilian; Stocks, Michael; Furber, Mark; Zhu, Jieping; Masson, Géraldine
Abstract A highly stereoselective three‐component Povarov reaction, catalyzed by (R)‐ and (S)‐BINOL hydrogen phosphate, was achieved for the first time with aminopyrroles and aminopyrazoles as 2‐azadiene precursors. A variety of aldehydes, enecarbamates, amino‐substituted azines participated in the reaction to afford the tetrahydropyrrolopyridines and tetrahydropyrazolopyridines in good yields with excellent diatereo‐ and enantioselectivities. A stereochemical model is proposed to account for the observed absolute stereochemistry. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>